The Activities of Improving English Speaking Skills in English Club SMA Negeri 1 Luwu - Jufri, Ismubaraqah; Amin, Fatimah Hidayahni; Jefri, Riny (Journal of Excellence in English Language Education, 2024)
This study uses a descriptive qualitative method that aims to find out the activities of improving English speaking skills in English Club SMA Negeri Satu (Smansa) Luwu. The results of the data obtained show that there are three activities in English Club Smansa 1 Luwu such as discussion, playing games, and storytelling. Discussion and storytelling activities are the most influential activities in improving the learners’ English-speaking skills. In this discussion activity, it can be seen that there are several stages carried out, such as grouping, looking for discussion topics, group discussion, and group presentation. Next is storytelling, in this activity the learners are given their respective roles to appear in front of the other learners, they must memorize the dialogue and practice the roles given by the leader. The stages of this activity are grouping, creating storytelling text, deciding the roles, and group performances. Based on the results of the study, it can be concluded that discussion and storytelling are activities that can improve the learners’ English-speaking skills in English Club Smansa 1 Luwu, where it can be seen that the learners have gained new knowledge about the components of speaking English such as vocabulary and pronunciation. Therefore, they’re hoping that in the future English Club Smansa 1 Luwu can pay more attention to the lessons in each activity in the meetings which held every week.